Nitrogen removal characteristics of efficient heterotrophic nitrification-aerobic denitrification bacterium and application in biological deodorization. (November 2022) - Huan, Chenchen; Yan, Zhiying; Sun, Jiang; Liu, Yang; Zeng, Yong; Qin, Wei; Cheng, Yapeng; Tian, Xueping; Tan, Zhouliang; Lyu, Qingyang
Graphical abstract: Highlights: A highly efficient HN-AD strain HY-1 was identified as Paracoccus denitrificans. Maximum removal rate of NH4 +, NO2 – and NO3 – reached 17.33, 21.83 and 32.37 mg L −1  h −1 . Denitrification rate under anaerobic conditions was 14.56 mg L −1  h −1 . HY-1 was successfully applied in BTF reactor and 98.07% of NH3 was removed. The ionic concentration of NH4 + and NO3 – in BTF outflow was significantly reduced. Abstract: A heterotrophic nitrifying aerobic denitrifying (HN-AD) strain HY-1 with excellent capacity, identified as Paracoccus denitrificans, was isolated from activated sludge. HY-1 was capable of removing NH4 +, NO2 –, and NO3 – with the corresponding rate of 17.33 mg-N L −1  h −1, 21.83 mg-N L −1  h −1, and 32.37 mg-N L −1  h −1, as well as the mixture of multiple nitrogen sources. Meanwhile, HY-1 could execute denitrification function under anaerobic conditions with a rate of 14.56 mg-N L −1  h −1 . HY-1 required less energy investment, which exhibited average denitrification rate of 5.19 mg-N L −1  h −1 at carbon–nitrogen ratio was 1. After nitrification–denitrification metabolic pathway analysis, HY-1 was applied in a biological trickling filter reactor for compost deodorization. The results showed that adding of HY-1 greatly reduced the ionic concentration of NH4 + and NO3 – in the circulating liquid without impairing the deodorization effect (NH3 removal rate＞98.07%). These findings extend the field of application of HN-AD and provide new insights for biological deodorization.